Effect of carbamide peroxide at different concentrations on the microhardness of bovine enamel - Casma Becerra , Juan Raul (2024)
Objectives: To compare the effect of bleaching agents based on carbamide peroxide in different concentrations on the microhardness of bovine enamel. Material and Methods: In vitro study. 60 samples of bovine enamel were used, divided into two groups according to the assigned agent: carbamide peroxide (Opaslescense PF, Ultradent), at 35% and 15%. Next, the bleaching agent was applied to the samples, according to the manufacturer's instructions. The surface microhardness of enamel was evaluated by Vickers microhardness test, before and after application of the bleaching agent. The relationship between variables was evaluated using Student's t-test. Results: The study found no significant differences between the microhardness groups treated with 15% and 35% carbamide peroxide, both at the beginning and after the application of the bleaching agent (p:0.160 and p:0.584 respectively). However, when considering the concentrations separately, both bleaching agents caused a decrease in the microhardness of the enamel (p<0.001 in both cases).  Conclusions: Both bleaching agents caused a decrease in the superficial microhardness of the enamel, the effect was similar for both concentrations.